REORGANIZATION OF THE PROCESS OF CONTROLLING THE END POSITION OF THE AIRCRAFT, WHICH RECEIVED DAMAGE TO THE SUPPORTING SURFACE - Казак, В. М. (Proceedings of National Aviation University (archive), 2021)
A solution to the problem of organizing the process of managing the final position is proposed aircraft in the event of possible damage to its bearing surfaces.